Effect of extraction agens on concentracion of organochlorine pesticides in drinking water - Stojceva-Radovanovic, Blaga; Marinovic, Dragan (Macedonian Journal of Ecology and Environment, 2001)
In this study was investigated the concentration of organochlorine pesticides in the drinking water was done of two agricultural localities near Kraljevo (Serbia, Yugoslavia) during 1998. The samples were extracted with three aprotic solvents: methylenechloride, n-hexane and petroleum ether and were analyzed gas chromatographic with capillary column and ECD accordance with USA EPA 608. The investigation shows that the best results are obtained when methylenechloride are used as extraction agens.The obtained concentration values were in range of 0,2424-0,3648 µg·cm3 Conclusion is that investigated drinking water is safe and suitable for consumption.